Legal Certainty Regarding the Legal Status of Riau Tabir Batik Based on Law Number 28 of 2014 on Copyright - Endang Suparta; Ismansyah; Runtung; Saidin (Publikasi Indonesia, 2025)
Initially, the only known batik was hand-drawn batik. Along with the increasing use of batik, batik technology has also developed rapidly.Now, in addition to traditional batik making, there is also